2018
DOI: 10.12998/wjcc.v6.i11.441
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of elevated serum carbohydrate antigen 199 level in acute cholangitis secondary to choledocholithiasis

Abstract: AIMTo investigate the diagnostic value of abnormal serum carbohydrate antigen 199 (CA199) level in acute cholangitis secondary to choledocholithiasis.METHODSIn this retrospective cohort study, the clinical data of 727 patients with choledocholithiasis admitted to the Third Affiliated Hospital of Zunyi Medical College from June 2011 to June 2017 were collected. Among these patients, 258 patients had secondary acute cholangitis and served as observation group, and the remaining 569 choledocholithiasis patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…22 Mei et al showed that elevated serum CA 19-9 levels were an important diagnostic indicator of acute cholangitis, secondary to CBD stones. 23 In this study, we found that CA 19-9 levels were significantly higher in group A than in group B (P < 0.05). However, CA 19-9 was not associated with stone retention or spontaneous passage.…”
Section: Discussionsupporting
confidence: 44%
“…22 Mei et al showed that elevated serum CA 19-9 levels were an important diagnostic indicator of acute cholangitis, secondary to CBD stones. 23 In this study, we found that CA 19-9 levels were significantly higher in group A than in group B (P < 0.05). However, CA 19-9 was not associated with stone retention or spontaneous passage.…”
Section: Discussionsupporting
confidence: 44%
“…When AC occurs, the serum concentration of CA199 is significantly increased, and this increase is positively correlated with the severity of cholangitis, which can therefore be used as a predictor of AC ( 35 ); a finding that was consistent with the results of the present study. It has also been shown that CA199 has certain reference value for the diagnosis of AC when it reaches a level of 52.50 kU/l ( 36 ). In the present study, there were two cases where the CA199 values were >12,000 kU/l.…”
Section: Discussionmentioning
confidence: 99%
“…8 For example, the increase of CA19-9 can also be seen in conditions such as pancreatic cancer, 9 chronic pancreatitis, cholelithiasis, 10 and cholangitis. 11 The rise in CA19-9 in these diseases is a result of obstruction causing the CA19-9 secreted by the normal bile duct, or pancreatic epithelium, flow into the bloodstream. 10 Therefore, researchers used the total bilirubin level to calibrate CA19-9, which can rule out the effect of obstructive biliary disease on the increase of CA19-9.…”
Section: Introductionmentioning
confidence: 99%